HERPETOFAUNA DAN HABITATNYA DI AREA FAKULTAS KEHUTANAN UNIVERSITAS PAPUA, MANOKWARI - Denisa Melanesia Kreglika Taran; Saremay Max Romario Sawaki; Marsia Adeleida Regina Rumatray; Fransiskus Hernandes Taran; Darius Yulian Ayamiseba (Forestry Study Program University Of Mataram, 2023)
Herpetofauna is a group of animal that make up the ecosystem and has an important role both ecologically and economically. Along with the fragmentation of ​​the Faculty of Forestry area at the University of Papua due to campus development, the diversity of the existing Herpetofauna may change. Therefore, this study aims to investigate the diversity of Herpetofauna and the habitat in the area of Faculty of Forestry at the University of Papua. The collection of data was carried out for one month using visual encounter survey with timed count technique. The results showed that there were 14 species of Herpetofauna consisting of one species of Frog (Platymanthis papuensis), ten species of lizards (Sphenomorphus muelleri, Sphenomorphus jobiensis, Emoia caeruleocauda, ​​Emoia jakati, Eutrophis multifasciata, Nactus pelagicus, Lemprolephis smaragdina, Cyrtodactylus sp., Gehira sp. and Hemydactylus frenatus) and three species of snakes (Micropechis ikaheka, Boiga irregularis and Candoia carinata). The most of Herpetofauna were found in the Arboretum Fahutan, seven species. Amphibians are only found at night while lizards and snakes were discovered both during the day and at night.